Can the Neoclassical Model Explain the Distribution of Foreign Direct Investment Across Developing Countries? - Zebregs, Harm (IMF Working Papers; Working Paper ;, 1998)
Since the beginning of the 1990s, foreign direct investment (FDI) in developing countries has increased dramatically. The distribution of FDI flows across these countries, however, is highly uneven; only a small number attract comparatively large amounts of foreign capital. This paper investigates whether the pattern of FDI flows can be explained by the standard neoclassical model or by modified versions of this model that allow for differences in production technologies across countries. The results suggest that the standard neoclassical approach is not particularly useful if we want to understand FDI flows to developing countries.